Shaky foundations: Refugees in Vancouver's housing market. (3rd December 2013) - Francis, Jenny; Hiebert, Daniel
Abstract Our purpose in this article is to examine refugees' access to housing in metropolitan Vancouver. How are refugees faring in Vancouver's housing market relative to non‐humanitarian immigrants? Is there evidence that their housing circumstances change over time? Following from this, can we detect systematic differences in housing experiences between refugees selected and supported by the Canadian government versus those who come to Canada seeking asylum? Finally, what are the most important barriers for refugees in Vancouver's housing market and how are they addressed? Our study involved three main forms of data collection: focus groups with representatives of organizations that support newcomers, focus groups with newcomers, and a systematic survey exploring the housing experience of immigrants and refugees. While this article focuses on the survey results, we also draw upon the contextual knowledge obtained through the focus groups. We find that refugees are more likely than economic immigrants to lack the resources needed to access adequate and affordable housing. Many inhabit inadequately maintained, overcrowded, and unaffordable housing units and experience increased risk of homelessness. Therefore, we conclude that there is a need for greater coordination between housing and settlement policy to enable all newcomers to meet their housing needs.